On the Tethyida (Porifera, Demospongiae) from Bahia State, northeast Brazil, with descriptions of two new species, taxonomic appointments and new records - Mácola, Rosa; Menegola, Carla (Zootaxa, 2018)
The recently proposed order Tethyida is characterized by the presence of megasclere styles, tylostyles or oxeas arranged in tracts ending as bouquets at or near the surface, and microsclere euasters. Two new species are described from the shallow coastal reefs (0–10 m) of Bahia, Brazil. Timea kamasary sp. nov. is represented by thin sciaphylous specimens with three categories of spicules: tylostyles, spined spheroxyasters and spined/smooth oxyasters in varied sizes. This species differs from Timea unistellata (Topsent, 1892) by having a different category of oxyasters. Tethya bitylastra sp. nov. is characterized by having strongyloxeas I and II, spherasters, oxyasters I and II, strongylasters and two categories of tylasters. This new species differs from Tethya maza Selenka, 1879 by having a second category of tylaster. Furthermore, we present taxonomic appointment for Timea berlincki (Leite, Fonseca, Leal & Hajdu, 2015) and Tethya maza and the first record of Timea stenosclera (Hechtel, 1969) for the Southwest Atlantic.